Squeaking of art : the mice go to the museum - Wellington, Monica (Dutton Children's Books, 2000)
Mice visit a museum and admire famous works of art in the different galleries, each of which is devoted to a specific subject or theme. Includes information about the paintings and where they may be found in real life.